Climate Variability Rather Than Livestock Grazing Dominates Changes in Alpine Grassland Productivity Across Tibet - Li, Meng; Wu, Jianshuang; Feng, Yunfei; Niu, Ben; He, Yongtao; Zhang, Xianzhou (Frontiers in Ecology and Evolution, 2021)
Alpine grasslands on the Tibetan Plateau, being vulnerable to environmental and anthropogenic changes, have experienced dramatic climate change and intensive livestock grazing during the last half-century. Climate change, coupled with grazing activities, has profoundly altered alpine grassland function and structure and resulted in vast grassland degradation. To restore degraded grasslands, the Central Government of China has implemented the Ecological Security Barrier Protection and Construction Project since 2008 across the Tibetan Autonomous Region. However, the relative effect of climate change and grazing activities on the variation in alpine grassland productivity is still under debate. In this study, we quantified how aboveground net primary production (ANPP) varied before (2000‒2008) and after (2009‒2017) starting the project across different alpine grasslands and how much variance in ANPP could be attributed to climate change and grazing disturbance, in terms of temperature, precipitation, solar radiation, and grazing intensity. Our results revealed that Tibet's climate got warmer and wetter, and grazing intensity decreased after starting the project. Mean ANPP increased at approximately 81% of alpine grasslands in Tibet, from 27.0 g C m-2 during 2000‒2008 to 28.4 g C m-2 during 2009‒2017. The ANPP positively correlated with annual temperature and precipitation, but negatively with grazing intensity for both periods. Random forest modelling indicated that precipitation explained about 29.0% of the grassland ANPP variance, about twice the proportion explained by grazing intensity. Therefore, precipitation variability was the key factor for alpine grassland ANPP increase across Tibet.